Course of depressive symptoms and treatment in the longitudinal assessment of bariatric surgery (LABS‐2) study. (25th March 2014) - Mitchell, James E.; King, Wendy C.; Chen, Jia‐Yuh; Devlin, Michael J.; Flum, David; Garcia, Luis; Inabet, William; Pender, John R.; Kalarchian, Melissa A.; Khandelwal, Saurabh; Marcus, Marsha D.; Schrope, Beth; et al.
<x xml:space="preserve">Abstract</x> Objective To examine changes in depressive symptoms and treatment in the first 3 years following bariatric surgery. Methods The longitudinal assessment of bariatric surgery‐2 (LABS‐2) is an observational cohort study of adults (n = 2, 458) who underwent a bariatric surgical procedure at 1 of 10 US hospitals between 2006 and 2009. This study includes 2, 148 participants who completed the Beck depression inventory (BDI) at baseline and ≥ one follow‐up visit in years 1‐3. Results At baseline, 40.4% self‐reported treatment for depression. At least mild depressive symptoms (BDI score ≥ 10) were reported by 28.3%; moderate (BDI score 19‐29) and severe (BDI score ≥30) symptoms were uncommon (4.2 and 0.5%, respectively). Mild‐to‐severe depressive symptoms independently increased the odds (OR = 1.75; P = 0.03) of a major adverse event within 30 days of surgery. Compared with baseline, symptom severity was significantly lower at all follow‐up time points (e.g., mild‐to‐severe symptomatology was 8.9%, 6 months; 8.4%, 1year; 12.2%, 2 years; 15.6%, 3 years; ps < 0.001), but increased between 1 and 3 years postoperatively (P < 0.01). Change in depressive symptoms was significantly related to change in body mass index (r = 0.42; P < 0001). Conclusion Bariatric surgery has a positive impact on depressive features. However, data suggest some deterioration in improvement after the first postoperative year. LABS‐2, #NCT00465829, http://www.clinicaltrials.gov/ct2/show/NCT00465829.